(untitled) (Journal of the College of Basic Education, 2023)
The scholars of grammar, language and morphology are the most important signs in the Arab history.through their dissertations on semantics, which prompted Western scholars who are specialists in this fieldThe likes of Palmer, Pierre Giraud, and Olman to benefit from the aforementioned Arab flag and transform it intoUseful issues in audio and video for the service of humanitysignal.The morphological connotation is an important part of this science, and based on what was mentioned, I studied my nameThe subject and the object a semantic study from the morphological point of view to monitor what morphological changes suggestof new meanings according to this change.The research was divided into two parts, the first for the subject noun and the second for the object noun with the introduction ofIn conclusion, the section on the subject’s name included talking about it and then its indication of lineage.The second part came, and I began to talk about the morphological significance of the plural noun.Acceptance, and God is the conciliator.